Psychotic symptoms in bipolar disorder: Two years’ retrospective study (Health Renaissance, 2017)
Background: Psychosis in bipolar disorder is common but still not well understood. There is paucity of literature from our country and none from this institute which serves the eastern part of Nepal.Objective: To describe the hallucinations and delusions in bipolar disorders in our place.Methods: Patients-record files of bipolar disorders with psychosis discharged in two years’ time from 2012 to 2014 were analysed. Patients with unipolar depression, recurrent depressive disorder, serious organic illness, and primary substance use disorders were excluded. Information was collected in a structured performa. Association of delusion and hallucination was observed.Results: During the study period, ninety-five patients with bipolardisorder had psychosis. Hallucination was present in 29 (30.5%) cases, and out of these 23 (79.3%) were cases of mania. In 26 (89.7%) patients, the hallucinations were mood congruent. The median duration of appearance of hallucination was 10 days and appeared early in mania. Among hallucinations, auditory verbal hallucinations were present in all 29 patients. Delusions were present in 77 (81.1%) of patients, and grandiose delusions were the most common. Grandiose delusions tended to occur even in the absence of hallucinations. Conclusion: Psychosis is common in bipolar disorder. Grandiose delusions are the most common delusion and are relatively independent of hallucination. The auditory verbal hallucinations are the most common type of hallucination. Hallucinations in mania tend to manifest earlier than in bipolar depression and mixed episode, and most of the hallucinations in bipolar disorder are mood congruent. Health Renaissance 2015;13 (1): 49-57